Selecting stories to tell: the gatekeeping of international news at SAfm - Ticha, Abel Akara (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2007)
The premise of this thesis is that the selection of international news to be aired on the bulletins of SAfm by SABC Radio News staff is influenced by more complex factors than could be seen solely from the prism of an empirical journalistic paradigm. Drawing from data obtained through participant observation and interviewing, it is noted that there has been a revolution from a propagandist approach during apartheid to a professional approach following the demise of apartheid, in the selection of international news for bulletins on SAfm. Using Lewin's theory of forces in decision making and locating it within four out of five levels of a framework of gatekeeping analysis provided by Shoemaker (1991) and Shoemaker et al (200 I), it is concluded that the delimiting well-tested routines of newsmaking act as powerful companions of individuals' selection decisions of international news broadcast on SAfm's bulletins. However, these routines are adapted to meet the organisational demands of the SABC, which as a Public Service Broadcaster (PBS) has embraced the discourse of South African nationalism/panAfricanism, as a major philosophy underpinning the Corporation's coverage of the world. Therefore, some individual, routine and organisational factors influencing the se lection of international news broadcast on SAfm's bulletins, are predetermined and co-determined by the social system (the ideological/discursive structure), which is promoted by certain social institutions. Instances of spokespersons of such institutions as governments, international governmental and non-governmental organisations, etc., officiating the news abound; the gatekeepers use them to meet routine professional standards of journalism. This potentially works to sustain the hegemonic discourses of the powerful in international affairs (in tenns of core/peripheral nations relations, and elite classlruled majority relations) though there is a conscious oppositional effort to modify or dwarf stories that explicitly promote imperialism and to hold rulers accountable to the public. It is posited that the time is ripe for newsworkers responsible for the production of bulletins for SAfm to take the risk that may be necessary to inject a few changes in routine practices that could limit the engineering of consent to the powerful elites in the international arena.
Keywords: South African Broadcasting Corporation; SAfm (South Africa); Radio broadcasting -- South Africa; Foreign news -- South Africa; Radio journalism -- South Africa